Antibacterial, cyto and genotoxic activities of A22 compound ((S-3, 4 -dichlorobenzyl) isothiourea hydrochloride). (October 2016) - Bonez, Pauline C.; Ramos, Andiara P.; Nascimento, Kátia; Copetti, Priscila M.; Souza, Márcia E.; Rossi, Grazielle G.; Agertt, Vanessa A.; Sagrillo, Michele R.; Santos, Roberto C.V.; Campos, Marli Matiko A.
Abstract: The A22 is a chemical compound that acts as a reversible inhibitor of a bacterial cell wall protein MreB leading the rods to the coccoid form. Thus, by changing the bacterial form, many properties can be affected, as the acquisition of nutrients, cell division, the clamping surfaces, motility and pathogenesis. Infections caused by strains of Pseudomonas aeruginosa have great clinical importance because these microorganisms can include more than one resistance mechanism acting together, limiting treatment options. Thus, it is important to investigate the action of A22 against P. aeruginosa, once there are urgent needs for new antimicrobial compounds for increase the arsenal therapeutic to treat diseases caused by this microrganism. Therefore, this study investigated for the first time the antimicrobial activity of A22 against seve standards strains of Gram negative microorganisms and twenty-eight clinical isolates of P. aeruginosa . This study performed an additional investigation to analyze the cyto and genotoxic potential effects from A22 on human peripheral blood mononuclear cells (PBMCs). The antibacterial activity of A22 was studied by broth microdilution method and time-kill assay. The cytotoxicity was evaluated by MTT assay at 24, 48 and 72 h of exposure to A22 and the genotoxicity was evaluated by the Comet assay. The susceptibility tests showed A22 has a relevant antibacterial activity against P. aeruginosa, including multidrug-resistant (MDR) clinical isolates. The A22 treatment not showed genotoxic effects against PBMCs in almost all concentrations tested at 24 and 48 h of exposure. Only for concentration of 32 μg/mL (highest tested) the damage index was significantly higher in all moments. The MTT assay demonstrated that A22 was able to maintain cell viability in all exposure times. In summary, the A22 demonstrated important anti- Pseudomonas activity and showed no cyto and genotoxic significant effect. These results need to be considered in future in vitro and in vivo studies in order to introduce the A22 as a possible therapeutic option. Highlights: A22 was presented as a promising antimicrobial agent. The MreB protein appears as a new therapeutic target to combat the growing bacterial resistance. Low geno and cytotoxicity presented by A22 encourages further study.